2017
DOI: 10.1016/j.euf.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Biosensor Assay for Rapid Uropathogen Identification and Phenotypic Antimicrobial Susceptibility Testing

Abstract: Background Standard diagnosis of urinary tract infection (UTI) via urine culture for pathogen identification (ID) and antimicrobial susceptibility testing (AST) takes 2–3 d. This delay results in empiric treatment and contributes to the misuse of antibiotics and the rise of resistant pathogens. A rapid diagnostic test for UTI may improve patient care and antibiotic stewardship. Objective To develop and validate an integrated biosensor assay for UTI diagnosis, including pathogen ID and AST, with determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 16 publications
0
42
0
2
Order By: Relevance
“…Analysis of all probes used for pathogen identification showed an overall sensitivity of 98.5% and specificity of 96.5%. Categorical and essential agreement with clinical microbiology of 97.6% for each factor were achieved for ciprofloxacin MIC 119 . In a variation of this biosensor-based AST, the level of precursor rRNAs (pre-rRNAs), an intermediate state in the formation of mature rRNA and a marker for cell growth, is assessed.…”
Section: Emerging Diagnostic Platformsmentioning
confidence: 81%
See 2 more Smart Citations
“…Analysis of all probes used for pathogen identification showed an overall sensitivity of 98.5% and specificity of 96.5%. Categorical and essential agreement with clinical microbiology of 97.6% for each factor were achieved for ciprofloxacin MIC 119 . In a variation of this biosensor-based AST, the level of precursor rRNAs (pre-rRNAs), an intermediate state in the formation of mature rRNA and a marker for cell growth, is assessed.…”
Section: Emerging Diagnostic Platformsmentioning
confidence: 81%
“…An electrochemical biosensor platform for UTI diagnostics has been extensively investigated, including investigating its direct application to clinical samples 119,120 (FIG. 2b,c).…”
Section: Emerging Diagnostic Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that species-specific detection of pathogens from clinical urine samples could be achieved in less than 6 h, and identification was demonstrated for 98% of Gram-negative bacteria for which species-specific probes were available, and causative agents in polymicrobial infections could also be identified. 34, 35 …”
Section: Diagnostic Tests For the Identification Of Bacterial Pathogensmentioning
confidence: 99%
“…The use of ternary mixed monolayers comprising two different thiols as diluents/spacers together with an appropriate SHCP self‐assembled on gold electrodes provides interfaces with extremely attractive characteristics for electrochemical biosensing of target nucleic acids hybridization,,,, and aptasensing …”
Section: Rational Design Of Surface Chemistrymentioning
confidence: 99%